Pengendalian Proses Produksi Untuk Meningkatkan Kualitas Produk Pada Usaha Out Of The Box Di Kota Palu - Devi Nurfatimah; Asngadi Asngadi; Sulaeman Miru; Syamsuddin Syamsuddin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Controlling the production process is very important in improving product quality, especially in out of the box businesses. This research aims to find out how to control the production process in this business to improve product quality. To be able to answer the problem formulation in the research, qualitative analysis techniques were used, namely the data reduction stage, data presentation and drawing conclusions. The results of data analysis show that the company has not been able to control the production process properly.